Comparative Seismic Assessment Methods for Masonry Building Aggregates: A Case Study - Chieffo, Nicola; Formisano, Antonio (Frontiers in Built Environment, 2019)
Recent seismic events produced considerable socio-economic losses. An important step for the reduction and mitigation of seismic risk in urban areas with a high population density is the assessment of global vulnerability of clustered buildings. The proposed work aims at appraising the seismic vulnerability of building aggregates within the historical centre of Arsita, damaged by the L'Aquila earthquake (2009 April 6th), through a multi-level approach deriving from the application of different estimation procedures. In particular, the seismic vulnerability quantification has been done by comparing three distinct methods, namely the macroseismic approach according to the EMS-98 scale, the Vulnus methodology, developed by the University of Padua, and the mechanical approach derived from using the 3Muri software. The expected damage has been estimated in terms of fragility curves, respectively for the entire buildings compound and the individual structural units located in the corner and intermediate positions, in order to evaluate the beneficial or detrimental aggregate effect on the seismic behaviour of individual constructions examined.